PENERAPAN APLIKASI SISTEM INFORMASI SPASIAL UNTUK PENGELOLAAN PROGRAM TUBERKULOSIS DI PUSKESMAS GATAK DAN KARTASURA KABUPATEN SUKOHARJO - Noor Alis Setiyadi (JPM17: Jurnal Pengabdian Masyarakat, 2019)
The proportion of smear positive in 2013-2016 in Sukoharjo District was reported still high in case in 2015 where the cases was 63%. . The purpose this community engagement was to implement the surveillance information system of tuberculosis (TB) using online-spatial in order to support the health officers in community health care (Puskesmas) organizing the spatial TB data integrated better and precisely The decision maker in Puskesmas and health district would be assisted by this activity where it could provide the data base to support TB eradication programs. Method of activities involved the implementation to supervise and train how to apply the information system getting the reporting and recording of data as the national guideline written. The training program conducted were introducing of the software, training of the basic of system applied, and dissemination of data and their analysis from software used. and review of pr-test and post-test activities. Results of service are in the form of material delivery during implementation and training, namely; 1). The spatial database of TB is available in survey application 2). TB officers at the puskesmas, the head of the puskesmas and the head of the sub-sector of TB in the health department who attended greatly appreciated and accepted the activities and use of the survey application. 3).Presentation of data and analysis obtained from the use of the software used as well as the results of the improvement in the ability of success after training that is 66.67% and which is quite successful 33.33%